Research of dynamic RQ system M/M/1 with unreliable server - Voronina, N. M. (Information Technologies and Mathematical Modelling. Queueing Theory and Applications : 21st International Conference, ITMM 2022, Karshi, Uzbekistan, October 25-29, 2022 : revised selected papers)
The paper considers a single-line retrial queueing (RQ) system with an unreliable server controlled by a dynamic random multiple access protocol. A study of the prelimit probability distribution of the number of applications in orbit has been carried out. To study this system, the method of generating functions is used.